2021
DOI: 10.3390/math9212798
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Maintenance of the k-out-of-n System with Respect to Cost-Type Criterion

Abstract: In a previous paper, the problem of how the preventive maintenance organization for the k-out-of-n: F system could be used, in order to maximize system availability, was considered. The current paper continues these investigations using a different optimization criterion. The proposed approach is based on decision making theory for regenerative processes. We propose a general procedure for comparing different preventive maintenance strategies based on the ordered statistics distributions, aiming to choose the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Over time, numerous maintenance policies have been developed, with extensive research dedicated to the subject as indicated by various sources [9][10][11][12][13]. However, the conventional maintenance method of replacing a component only when it fails can prove to be too costly in terms of financial and time resources.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, numerous maintenance policies have been developed, with extensive research dedicated to the subject as indicated by various sources [9][10][11][12][13]. However, the conventional maintenance method of replacing a component only when it fails can prove to be too costly in terms of financial and time resources.…”
Section: Introductionmentioning
confidence: 99%
“…In some of our work the problems of preventive maintenance optimization for the subsea pipeline monitoring system with respect to availability maximization in [17] and with respect to cost-type criterion in [18] has been considered. In [19] it was proposed to use the risk tree as an assistant tool for the decision-maker.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of decision making and preliminary prophylactic analysis was considered in [32][33][34]. In some of our previous works [9,35,36], the problem of the sensitivity analysis of output model characteristics to the distributions of the input characteristics was considered. The papers of Z. Kala presented a general approach to the problems of sensitivity analysis [37,38].…”
Section: Introductionmentioning
confidence: 99%